2017
DOI: 10.1111/jpm.12408
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of the comparative effectiveness of smoking cessation medication among individuals with mental illness in community‐based mental health and addictions treatment settings

Abstract: Introduction Individuals with mental illnesses (MI) have diagnosis-specific reasons for smoking and achieve low smoking cessation when using cessation medications. Aim To assess differences in smoking cessation outcomes by MI diagnosis and cessation medications in outpatient mental health and addictions treatment settings in Vancouver, Canada. Method This is a retrospective analysis of tobacco treatment outcomes from 539 participants. The programme consists of cessation pharmacotherapy with 8 to 12 weeks of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…However, larger head‐to‐head studies are needed to test those hypotheses because some studies have found beneficial effects for bupropion in smokers with PTSD (Hertzberg, Moore, Feldman, & Beckham, ; McFall et al, ). Our finding is consistent with a retrospective, open‐label trial of varenicline (Okoli, Wiggins, Fallin‐Bennett, & Rayens, ), and a concurrent varenicline and prolonged‐exposure therapy trial in smokers with PTSD (Foa et al, ), both of which showed beneficial effects of varenicline in smokers with PTSD. They are also consistent with nonplacebo‐controlled trials of NRT (Hertzberg et al, ; Kelly et al, a; Kelly et al, b; McFall et al, ) showing beneficial effects in smokers with PTSD.…”
Section: Discussionsupporting
confidence: 90%
“…However, larger head‐to‐head studies are needed to test those hypotheses because some studies have found beneficial effects for bupropion in smokers with PTSD (Hertzberg, Moore, Feldman, & Beckham, ; McFall et al, ). Our finding is consistent with a retrospective, open‐label trial of varenicline (Okoli, Wiggins, Fallin‐Bennett, & Rayens, ), and a concurrent varenicline and prolonged‐exposure therapy trial in smokers with PTSD (Foa et al, ), both of which showed beneficial effects of varenicline in smokers with PTSD. They are also consistent with nonplacebo‐controlled trials of NRT (Hertzberg et al, ; Kelly et al, a; Kelly et al, b; McFall et al, ) showing beneficial effects in smokers with PTSD.…”
Section: Discussionsupporting
confidence: 90%
“…These intervention programs include telephonebased, web-based, or combined telephone and web-based counseling. In the study by Ocoli et al, it was stated that these intervention programs were as effective as medical treatment (C. Okoli, Wiggins, Fallin-Bennett, & Rayens, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, combination therapy of VAR and OTC NRT cannot be identified. Clinical trials have shown better efficacy of VAR in combination with NRT than VAR alone [45]; however, an analysis of patients who attended tobacco treatment programs in Canada showed a similar abstinence rate among dual VAR and NRT users, dual NRT users, and single NRT users [23]. With mixed results in the literature and unknown patterns of prescription and OTC NRT, the expected real-world impact of the unbalanced missing information is uncertain.…”
Section: Discussionmentioning
confidence: 99%